KOMUNITAS POSITIVE PARENTING “POPSTAR” UNTUK MENINGKATKAN KUALITAS PENGASUHAN - Mauna; Ernita Zakiah; Zarina Akbar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract The Covid-19 pandemic has resulted in many changes, including more time for parents to interact with their children. The increasing duration of togetherness among family members should be able to improve the quality of interaction between family members. In fact, there is an increasing problem stemming from disharmony in the relationship between children and parents. One of the causes of this problem is the unpreparedness of family members to face changes and the lack of information for parents about positive parenting. The existence of a positive parenting community